2021
DOI: 10.4274/tjod.galenos.2021.58997
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the association of the ACE I/D and PAI-1 4G/5G polymorphisms with recurrent pregnancy loss in Iranian women: Are the investigations adequate?

Abstract: The associations of ACE I/D and PAI-1 4G/5G polymorphisms with recurrent pregnancy loss (RPL) in Iranian women have yielded controversial results. Thus, we conducted a meta-analysis to obtain more certain results. A comprehensive literature search was performed in the PubMed, Web of Sciences, Scopus, MedRxiv, SID, and CNKI databases up to January 1st, 2021, using the appropriate terms. All case-control studies were included. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to estimate the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Decreased FGF-1 expression has been shown in the endometrium of patients with RIF, which is mainly necessary for implantation in the luteal phase. [ 16 ] It has been shown that FGF signalling is important for the maturation and regeneration of endometrium following menstruation. [ 17 ] Changes in the expression of FGF-1 in infertile women have been documented, which shows that FGF-1 is an important maternal factor affecting implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased FGF-1 expression has been shown in the endometrium of patients with RIF, which is mainly necessary for implantation in the luteal phase. [ 16 ] It has been shown that FGF signalling is important for the maturation and regeneration of endometrium following menstruation. [ 17 ] Changes in the expression of FGF-1 in infertile women have been documented, which shows that FGF-1 is an important maternal factor affecting implantation.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reported that ACE I/D polymorphism had an obvious correlation to RSA, showing that PAI-1 4G/5G had high clinical heterogeneity but did not have an association with RSA [119]. Another metaanalysis concluded that the frequencies of 4G/4G and 4G/5G alleles in RSA patients were higher, which was more obvious in Asian and African groups [120]. Studies also pointed out that ACE I/D and PAI-1 4G/5G polymorphisms were associated with RSA in Iranian and Polish women [121,122].…”
Section: Ace (I/d) and Pai-1 (4g/5g)mentioning
confidence: 99%